Exotoxins A, T and S among Pseudomonas Aeruginosa Isolates from Clinical and Hospital Environment Samples - Ahmed Jamal Hussein; Frial Gemeel Abd (Journal of Global Pharma Technology, 2017)
Pseudomonas aeruginosa is one of the most widely recognized Gram-negative opportunistic pathogens related with nosocomial infections. The presence of several virulence factors, for example, exotoxins of the bacteria making a genuine risk to the patient. This study was intended to detect Exotoxin A, T and S genes in P. aeruginsoa isolates utilizing PCR system. It includes (30) isolates of bacteria diagnosed by traditional techniques and confirmed by the API 20Eand Vitek 2 Systems , DNA isolated and subjected to amplify using specific primers for bacteria. The consequences of PCR amplification for the genes encoding for exotoxin A, T and S demonstrated that all P. aeruginosa isolates showed the presence of the genes encoding for exotoxin A and exotoxin T corresponding to 100 % of the isolates while twenty two (22) isolates comparing to 73.33 % of the total thirty (30) isolates were recorded to be positive for exotoxin S gene . It can be concluded that exotoxins are a conspicuous virulence factors for P. aeruginosa and responsible for a genuine threat to patients.Keywords: Exotoxin, Pseudomonas aeruginosa ,Toxin ,Environmental Isolate.